Story Mapping Strategy to Teach Reading Comprehension Achievement - Sundari Sundari; Zulaikah Zulaikah; Dwi Andriani (Channing : Journal of English Language Education and Literature, 2019)
The objective of this study was to find out whether or not there are any significant differences between students who are taught by using story mapping strategy and students who are not taught by using story mapping strategy in teaching reading comprehension at the tenth-grade students of MA Subulussalam OKU Timur. This study used an experimental method, by quasi-design. Meanwhile, the population was the tenth-grade students of MA Subulussalam Oku Timur with total students were 151. The sample was 71 students, consist of two groups, namely experimental class consist of 34 students, and control class consists of 37 students which chosen by using purposive sampling. In this study, the writer used SPSS 16 to analyze. The result of this research shows that the story mapping strategy was effective in teaching reading comprehension at the tenth-grade students of MA Subulussalam OKU Timur.